2015
DOI: 10.7314/apjcp.2015.16.15.6397
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure and Haematological Derangement in Cervical Cancer Cases in India

Abstract: Cervical cancer is the second most common gynecological malignancy worldwide. According to HPV Information Centre, Spain (Aug'2014), in India approximately 1,22,844 women are diagnosed with the disease every year and of them 67,477 die due to the disease. CaCx is said to be mediated by HPV but recent data published reveal the role of Oxidative Stress in different Cancers. Arsenic is also one of the agents for causing Oxidative Stress. Arsenic has been linked with different types of cancer. Arsenic is considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…The results reported here, together perhaps with that of Kumar et al [ 6 ], suggest that high concentrations of arsenic are biologically active in the development of squamous cell cancer of the cervix, and as such would warrant systematic investigation. Given the limited data on both HPV infection and on the proportion of cervical cancer cases with such infection in Bangladesh, a large-scale trial to assess the efficacy of screening in areas with both high and low arsenic concentration in well water, with urinary arsenic measurement and HPV characterization in cases and referents, would contribute greatly to knowledge of cervical cancer causality and management in Bangladesh and of the role of arsenic in its evolution.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The results reported here, together perhaps with that of Kumar et al [ 6 ], suggest that high concentrations of arsenic are biologically active in the development of squamous cell cancer of the cervix, and as such would warrant systematic investigation. Given the limited data on both HPV infection and on the proportion of cervical cancer cases with such infection in Bangladesh, a large-scale trial to assess the efficacy of screening in areas with both high and low arsenic concentration in well water, with urinary arsenic measurement and HPV characterization in cases and referents, would contribute greatly to knowledge of cervical cancer causality and management in Bangladesh and of the role of arsenic in its evolution.…”
Section: Discussionsupporting
confidence: 72%
“…There are essentially no data against which to compare the results of the current study. The only paper identified that addressed the relation between arsenic in drinking water and cervical cancer (in women in Patna, India) reported that mean blood arsenic concentration was higher, at 100.7 ppb, in 51 cervical cancer patients than in 48 healthy referents (arsenic concentration not given) [ 6 ]. The IARC reviews in 2004 [ 1 ] and 2008 [ 2 ] included only one study that had cervical cancer as an endpoint, with six deaths [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…147 As-induced OS in patients with carcinoma of cervix has an association with red blood cell count and hemoglobin level, and the high level of As increases OS in the patients, and increases malondialdehyde (MDA) levels in patients with cervix cancer. 148 Many living cells can convert arsenite to arsenate through oxidation, which generates two electrons for the formation of H 2 O 2 . H 2 O 2 produces OHby Fenton reaction, a very active oxygen radical according to a wide range of macromolecule oxidation.…”
Section: As Implicationmentioning
confidence: 99%